(untitled) (The Review of Diabetic Studies, 2024)
Nursing professionals are at the heart of Saudi Arabia’s healthcare system, providing essential care and supporting public health initiatives to help the country meet its national health goals. However, nurses often face challenges such as staff shortages and limited opportunities for leadership, which stem from prevailing attitudes that limit their influence on healthcare policy. This study explores the current status of nursing in Saudi Arabia and proposes practical strategies to empower nurses as leaders in the field. Encouraging their involvement in decision-making and policy development is vital for building a resilient and effective healthcare system in line with the goals of Vision 2030.